LOGO AS A MINIATURE PAINTING: INTEGRATION OF DRAWING STRUCTURE, PICTORIAL COLOR LANGUAGE, AND COMPOSITIONAL BALANC - Рублевська, Н.В.; П’єх, Р.М.; Цуп, А.В. (SWorldJournal, 2025)
This article is theoretical in nature and explores the logo as an artistic object that integrates elements of drawing structure, pictorial color language, and compositional balance. The logo is viewed not merely as an element of visual identity, but as a